Audiobooks Implementation in an EFL Listening Classroom - Muhammad Arief Assiddiqhi; Rusdi Noor Rosa (Universitas Negeri Padang, 2021)
The development of technology should be followed by all aspects of human life, including education. One of the possibilities of adapting technology development in education is by designing digital learning materials. The aim of this paper is to discuss the ways of using audiobooks as a better replacement material to be used in an EFL listening classroom. Many students face difficulties in listening, like problems in their listening comprehension, having a hard time pronouncing words, and make the connection between what they listen to and what they have already known because they are unable to accurately comprehend spoken materials. Audiobooks give a solution to these complications by presenting them with a native speaker illustration, giving students the proper pronunciation of words. Overall, audiobooks are suitable for enhancing students’ listening comprehension capability and diminishing the fossilized problems they have been carried for so long.